ANALYZING TEACHERS’ ROLE IN SBDP LEARNING AT FIFTH GRADE OF ELEMENTARY SCHOOLS IN CLUSTER ONE KECAMATAN TAMPAN KOTA PEKANBARU - Hikmah Aulia Rizki; Zufriady Zufriady; Guslinda Guslinda (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This was a qualitative research aiming to describe the role of teachers in SBdP learning at fifth grade of elementary schools in cluster one Kecamatan Tampan Pekanbaru. The data were collected through observations, interviews, and documentations. The instruments were: observation sheets and interview guides referring to indicators of the role of teachers in learning and those instruments were validated by experts or validators. The subjects in this study were four fifth grade teachers of the elementary schools in Cluster one Kecamatan Tampan. It was found that teachers performed their role  in SBdP learning well but the implementation was not perfect yet. On the indicator of teacher as a demonstrator, teachers presented SBdP materials in theory and practice. Then, on the indicator of  teacher as a class manager, the teachers carried out SBdP learning in a thematic way and utilized scientific approach. Moreover, on the indicator of teacher as a mediator, they applied pianics, pictures contained in student books, as well as audio visual videos of the song of “Gugur Bunga” and the video of human circulatory system as the learning media. After that, on the indicator of teacher as a facilitator, the teachers implemented thematic printed books, worksheets books, and books of national compulsory songs as learning resources. Finally, on the indicator of teacher as an evaluator, teachers did not yet carry out quizes, portfolios, or project assessments, but they scarried out an assessment process.